Mapping conversations about land use: How modern farmers practice individuality. Issue 1 (1st June 2021) - Brock, Steen; Christensen, Andreas Aagaard; Hansen, Line Block; Graversgaard, Morten; Vejre, Henrik; Dalgaard, Tommy; Piil, Kristoffer; Andersen, Peter Stubkjær
In this article, drawing on the discursive psychology of Rom Harré, we show how mapping the exchange of words among people might disclose a complex reality; not merely that which farmers explicitly talk 'about' but the reality implicitly at stake within the communication. More specifically, we show how discourses involving modern farmers reveal an underlying placing in an abstract space, having sub-spaces defined by the life-orientation, sense of self and according self-positioning of modern people. In this way, we construct a road map of a set of 'individualities' characterizing the life of modern farmers: an individuality of citizenship, an individuality of geographies and an individuality of experience. Consequently, farmers face the problem that this multiplicity of individuality prevents them from communicating, as we will call it, univocally in the public by contrast to the univocal voices of other established social groups. We will analyse the structure of that problem by viewing diverse relations between the authority and the authenticity of different partners in the conversation on land use.